2015
DOI: 10.1063/1.4919893
|View full text |Cite
|
Sign up to set email alerts
|

Realization of optical bistability and multistability in Landau-quantized graphene

Abstract: The solution of input-output curves in an optical ring cavity containing Landau-quantized graphene is theoretically investigated taking the advantage of density-matrix method. It is found that under the action of strong magnetic and infrared laser fields, one can efficiently reduce the threshold of the onset of optical bistability (OB) at resonance condition. At non-resonance condition, we observed that graphene metamaterial can support the possibility to obtain optical multistability (OM), which is more pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 65 publications
0
22
1
Order By: Relevance
“…7 In general, the remarkable differences come from the denominator of Eqs. (12) and (17). In the limit γ → 0, the absorption edge can be changed by the field, which leads to the so called dynamic Franz-Keldysh effects.…”
Section: Methodsmentioning
confidence: 99%
“…7 In general, the remarkable differences come from the denominator of Eqs. (12) and (17). In the limit γ → 0, the absorption edge can be changed by the field, which leads to the so called dynamic Franz-Keldysh effects.…”
Section: Methodsmentioning
confidence: 99%
“…In Refs. [54][55][56][57][58][59][60][61][62][63] it has been demonstrated that the optical transitions between adjacent Landau levels in graphene for magnetic field 0.01-10 T fall into terahertz and infrared region according to…”
Section: Model and Equationsmentioning
confidence: 99%
“…Moreover, due to growing high quality epitaxial graphene and combination of uncommon electronic features with extraordinary optical properties, they are very favoraitable for applications in infrared and terahertz optics [51][52][53]. Some optical properties of graphene [54][55][56][57][58][59][60][61][62][63] based on the nonlinear optical interaction in the presence of strong magnetic field have been analyzed. For example, generation of polarization entangled photons [54], generation and propagation of ultraslow optical solitons [57,58], controlling the optical bistability and multistability [61][62][63] have been reported very recently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the interest in fundamental research of optoelectronic and condensed matter physics [1,4], graphene is gaining attention owing to its various technological applications [5][6][7][8][9]. Moreover, extant literature has reported investigations concerning the optical properties of graphene [10][11][12][13][14][15]. Not only do the investigations provide insights into the underlying nature of graphene's excited states, but they also open up interesting perspectives for emerging photonic and optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%